Peran Imajinasi Untuk Pendidikan Kristen yang Transformatif - Tiatira Teresa Dewantoro; Astri Kesuma Hati Sinaga (Sekolah Tinggi Teologi Simpson Ungaran, 2023)
Christian education is always meant to transform the lives of the students. However, the understanding of the superiority of ratio becomes the base of most educational practices, including Christian education. This understanding makes ratio the only aspect accommodated in a learning process. Nevertheless, the ratio is not the only aspect that needs to be accommodated by Christian education; there is also an extra-rational aspect that also plays a huge part in human life. Referring to the transformative learning theory by Jack Mezirow, reflective thinking is the key to transformative learning, which is very much influenced by human imagination. Amid the controversy about the destructive characteristic of imagination, imagination takes a massive role in transformative learning. The Christian perspective is also rooting for the use of imagination that is constructive in a learning process. So, the use of imagination in the right way is very effective in achieving transformative learning in Christian education.